2004
DOI: 10.1530/eje.0.1500905
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-dependent stimulation of adiposity and appetite by a ghrelin mimetic in the rat

Abstract: Objective: Chronic administration of GH secretagogues (GHSs) induces a state of positive energy balance in rodents by a GH-independent mechanism. Here we sought to determine to what extent the GHS effects to increase food intake and increase fat accumulation are glucocorticoid-dependent. Design: The effects of twice-daily s.c. injections of GH-releasing peptide-6 (GHRP-6) (250 mg/kg) for 2 weeks on body weight, food intake and fat pad weight were determined in both adrenalectomised (ADX) rats (with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
18
1
2
Order By: Relevance
“…In rodents, ghrelin administration activates a variety of stress-related behavioral and neuroendocrine responses. The ghrelin-induced increase of plasma glucocorticoids levels likely helps to cope with stress since glucocorticoids – similarly to ghrelin— increase glycemia, stimulate adiposity and enhance motivated behaviors (Dallman, 2010; Tschop et al, 2000; Tung et al, 2004). Notably, ghrelin signaling seems to be required for full activation of the HPA axis under some stress conditions (Chuang et al, 2011; Spencer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, ghrelin administration activates a variety of stress-related behavioral and neuroendocrine responses. The ghrelin-induced increase of plasma glucocorticoids levels likely helps to cope with stress since glucocorticoids – similarly to ghrelin— increase glycemia, stimulate adiposity and enhance motivated behaviors (Dallman, 2010; Tschop et al, 2000; Tung et al, 2004). Notably, ghrelin signaling seems to be required for full activation of the HPA axis under some stress conditions (Chuang et al, 2011; Spencer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…TSH and T4 levels were lower in the Lou/C rat, although T3 levels were not significantly different, indicating central hypothyroidism that would act to limit energy expenditure in response to low body weight and low serum leptin levels. Corticosterone is permissive for appetite stimulation and body fat accumulation, and the higher levels observed in the Wistar rat may stimulate adiposity via the actions of hormones such as ghrelin (Tung et al 2004). Thus, the lower levels of plasma corticosterone levels in the Lou/C may contribute to their lower levels of WAT.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, ghrelin, at concentrations within the normal physiological range, stimulates the HPA axis, increasing hypothalamic CRF mRNA expression and raising plasma corticosterone levels [42]. It has been suggested that glucocorticoids may have permissive effects for ghrelin’s orexigenic and fat-accumulating effects [43]. Anxiety and depression are often associated with stress.…”
Section: Ghrelin Leptin and A Link Between Stress Reward And Appetitementioning
confidence: 99%